2020
DOI: 10.1186/s12913-020-05569-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the healthcare pathway through patients’ experience and profiles: implications for breast cancer healthcare providers

Abstract: Background: Healthcare systems are facing many changes. Particularly, patients are more engaged in the care process. The medical perspective of the process is insufficient to provide patients with high quality care and service personalisation. This research presents an attempt to complete this medical perspective through an experiential perspective, especially for chronic diseases such as cancer. We investigated patients' experiences and profiles to reach a deeper understanding of their needs and expectations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 51 publications
0
36
0
Order By: Relevance
“…As perceived social support is influenced by the recipient's characteristics and pre-existent context (Collins and Feeney, 2004 ), it could be important to profile patients in terms of needs and personality traits so to develop ad-hoc resources for optimizing social support strategies. This would allow health professionals to work in conjunction with caregivers to raise awareness on the functions of social support and to identify the best support conducts to enact toward the patient (Cherif et al, 2020 ).…”
Section: Social Support and Injured Selfmentioning
confidence: 99%
“…As perceived social support is influenced by the recipient's characteristics and pre-existent context (Collins and Feeney, 2004 ), it could be important to profile patients in terms of needs and personality traits so to develop ad-hoc resources for optimizing social support strategies. This would allow health professionals to work in conjunction with caregivers to raise awareness on the functions of social support and to identify the best support conducts to enact toward the patient (Cherif et al, 2020 ).…”
Section: Social Support and Injured Selfmentioning
confidence: 99%
“…While the patient’s role in the course of the disease and in medical decision making is gaining interest, little research has focused on patient experiences [ 27 , 28 ]. Patient-centered care is an essential component of quality care that seeks to improve responsiveness to patients’ needs, values, and predilections and to enhance psychosocial outcomes, such as anxiety, depression, unmet support needs, and quality of life [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, few published studies address the experience of women with breast cancer from diagnosis to follow-up. These include a clinical pathway approach in the United Kingdom in the early 21st century [ 35 ], a breast cancer patient journey in Singapore [ 25 ], a netnography of breast cancer patients in a French specialized forum [ 28 ], a meta-synthesis of Australian women living with breast cancer [ 36 ], and a systematic review blending qualitative studies of the narratives of breast cancer patients from 30 countries [ 37 ]. Sanson-Fisher et al [ 29 ] concluded that previously published studies had examined limited segments of patients’ experiences of cancer care and emphasized the importance of focusing more on their experiences across multiple components and throughout the continuum of care.…”
Section: Introductionmentioning
confidence: 99%
“…This review focuses on studies that contribute to the definition and conceptualization of the concepts of patient trajectory, patient pathway or patient journey resulting in a theoretical and conceptual contribution. Thus, on the one hand, qualitative studies involving a single episode of care limited in time (a one-time treatment) or space (a single hospital service/department) were excluded to the extent that the care trajectory involves multiple points of interaction over time 26,27 and multiple organizational structures or intra-organizational entities along the care continuum 28 . On the other hand, studies with no theoretical or conceptual input were also excluded.…”
Section: Phenomena Of Interestmentioning
confidence: 99%